Efficient and Sustainable Platform for Preparation of a High-Quality Immunoglobulin G as an Urgent Treatment Option During Emerging Virus Outbreaks - Kurtović, Tihana; Ravlić, Sanda; Štimac, Adela; Mateljak Lukačević, Sanja; Hećimović, Ana; Kazazić, Saša; Halassy, Beata (Frontiers in Immunology, 2022)
During the pre-vaccine era of the COVID-19 pandemic convalescent plasma has once again emerged as a major potential therapeutic form of passive immunization that in specific cases still represents irreplaceable treatment option. There is a growing concern that variable concentration of neutralizing antibodies, present in convalescent plasma which originates from different donors, apparently affects its effectiveness. The drawback can be overcome through the downstream process of immunoglobulin fraction purification into a standardized product of improved safety and efficacy. All modern procedures are quite lengthy processes. They are also based on fractionation of large plasma quantities whose collection is not attainable during an epidemic. When outbreaks of infectious diseases are occurring more frequently, there is a great need for a more sustainable production approach that would be goal-oriented towards assuring easily and readily available immunoglobulin of therapeutic relevance. We propose a refinement strategy for the IgG preparation achieved through simplification and reduction of the processing steps. It was designed as a small but scalable process to offer an immediately available treatment option that would simultaneously be harmonized with an increased availability of convalescent plasma over the viral outbreak time-course. Concerning the ongoing pandemic status of the COVID-19, the proof of concept was demonstrated on anti-SARS-CoV-2 convalescent plasma but is likely applicable to any other type depending on the current needs. It was guided by the idea of persistent keeping of IgG molecules in the solution, so that protection of their native structure could be assured. Our manufacturing procedure provided a high-quality IgG product of above the average recovery whose composition profile was analyzed by mass spectrometry as quality control check. It was proved free from IgA and IgM as mediators of adverse transfusion reactions, as well as of any other residual impurities, since only IgG fragments were identified. The proportion of S-protein-specific IgGs remained unchanged relative to the convalescent plasma. Undisturbed IgG subclass composition was accomplished as well. However, the fractionation principle affected the final product's capacity to neutralize wild-type SARS-CoV-2 infectivity, reducing it by half. Decrease in neutralization potency significantly correlated with the amount of IgM in the starting material.